The Experience of VaccinarSinToscana Website and the Role of New Media in Promoting Vaccination - Boccalini, Sara (Vaccines (Basel), 2020)
The Department of Health Sciences (University of Florence) developed a regional website “VaccinarSinToscana” in order to provide information on vaccines and communicate with the general population, as well as the healthcare community, at a regional and local level. The aim of this paper is to present the VaccinarSinToscana website framework and analyze the three-year activity of the website and the related social network account on Facebook in terms of dissemination and visibility. In the first three years since its launch, the VaccinarSinToscana portal has increased its visibility: the number of single users, visits and single web pages has grown exponentially. Our results also demonstrate how the Facebook account launch contributed enormously to the increase in the visibility of the website. The objective for the future of the VaccinarSinToscana portal is to grow further, in order to reach out to an even wider audience.